(untitled) (Journal of Bangladesh Academy of Sciences, 2011)
This investigation analyses application of Lies scaling group of transformations to steady flow of a Newtonian fluid over a stretching sheet in presence of chemically reactive species with first order reaction. The governing partial differential equations reduced to self-similar nonlinear ordinary differential equations by the transformations. Obtained momentum equation is solved analytically and the concentration equation is numerically solved applying finite difference method with Thomas algorithm. The plotted results reveal that with the increase of Schmidt number as well as reaction-rate parameter causes a reduction in the thickness of the concentration boundary layer and also the concentration at a point decreases. DOI: http://dx.doi.org/10.3329/jbas.v35i1.7969 Journal of Bangladesh Academy of Sciences, Vol.35, No.1, 43-50, 2011